2001
DOI: 10.1111/j.1745-6584.2001.tb02482.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Natural Attenuation Experiment with a Petroleum Hydrocarbon NAPL Source

Abstract: A three-dimensional solute transport model with biological reactions is presented for simulating the natural attenuation study (NATS) at the Columbus Air Force Base in eastern Mississippi. NATS consisted of the release of a petroleum-based nonaqueous phase liquid (NAPL) and subsequent monitoring of BTEX (benzene, toluene, ethylbenzene, p-xylene), naphthalene, decane, and bromide in a shallow, unconfined aquifer. Conceptual and mathematical models were developed for NAPL source release, sequential aerobic/anaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…Such sequential depletion of TEA has been well documented in case of NAPL contaminant plumes in groundwater [29,72,73]. In fact, redox gradient has been shown to develop even on a pore scale, when Jakobsen 2007, indicated that separation of redox processes within a single average pore space is possible [65].…”
Section: Role Of Geometry Of Petroleum Deposits In Development Of Redmentioning
confidence: 92%
“…Such sequential depletion of TEA has been well documented in case of NAPL contaminant plumes in groundwater [29,72,73]. In fact, redox gradient has been shown to develop even on a pore scale, when Jakobsen 2007, indicated that separation of redox processes within a single average pore space is possible [65].…”
Section: Role Of Geometry Of Petroleum Deposits In Development Of Redmentioning
confidence: 92%
“…Examples can be found in Leij et al, (2000) and Domenico and Robbins (1985). Such modelling could be used as part of a model for bio-degradation as has been implemented in software like BIOSCREEN (United States Environmental Protection Agency, 1996), BIOPLUME (United States Environmental Protection Agency, 1998) and SEAM3D (Brauner and Widdowson, 2001) . There are three problems related to this approach.…”
Section: Description Of the Data And The Bio-degradation Processmentioning
confidence: 99%
“…Conventional methods of evaluating biodegradation in ground water comprise either static microcosm or flow-through column studies in the laboratory (Althoff et al, 2001), field-based estimates with reactive well tests (Istok et al, 1997;Istok et al, 2001;Haggerty et al, 1998), or field data analysis especially via numerical modelling (Brauner and Widdowson, 2001;Thornton et al, 2001;Huling et al, 2002;Prommer et al, 2002., Bockelmann et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the overall effect of mass transfer processes within the domain, the transient transport equation for the dissolving component under uniform flow conditions is given by (Schaerlaekens et al, 2000;Brauner and Widdowson 2001…”
Section: Governing Equationsmentioning
confidence: 99%